Alergia a ß-lactámicos en niños - Guzmán M., M. Antonieta; Tordecilla F., Rocío; González G., M. de los Ángeles (Revista Hospital Clínico Universidad de Chile, 2019)
Allergy to Betalactams is a widely suspected pathology, which is not regularly studied in Chile, leading to a misusage of antibiotics of other families. In this article a case report in a pediatric patient will be described, and a discussion about the studies needed for this pathology, and treatment will be made in accordance to the experiences and tools available in Chile, and specifically in University of Chile Clinical Hospital. In our Hospital we study these cases following international guidelines for the diagnosis of allergy to Betalactams.